A rapid cell-based assay for determining poloxamer quality in CHO suspension cell culture - Narayanappa, Athmaram Thimmasandra (BioTechniques, 2019)
Poloxamers are water-soluble polymers that are widely used in cell culture bioprocessing to protect cells against shearing forces. Use of poor-quality poloxamers may lead to a drastic reduction in cell growth, viabilities and productivities in cell culture-based manufacturing. In order to evaluate poloxamer quality and promote more consistent performance, a rapid cell membrane adhesion to hydrocarbon assay was developed based on the adhesive properties of cell membranes to selective hydrocarbons. The assay can identify a poor-performing poloxamer characterized by significant drop in viable cell density and percent viability. The assay was verified across multiple good and bad poloxamer lots, and the results were in agreement with established cell growth and high-performance liquid chromatography assays